Soil Organic Matter in Urban Areas of the Russian Arctic: A Review - Evgeny Abakumov; Alexey Petrov; Vyacheslav Polyakov; Timur Nizamutdinov (Atmosphere, 2023)
Polar ecosystems are the most important storage and source of climatically active gases. Currently, natural biogeochemical processes of organic matter circulation in the soil-atmosphere system are disturbed in urban ecosystems of the cryolithozone. Urbanized ecosystems in the Arctic are extremely under-investigated in terms of their functions in regulating the cycle of climatically active gases. The role of urban soils and soil-like bodies in the sequestration and stabilization of organic matter is of particular interest. The percentage of gravimetric concentrations of organic matter in Arctic urban soils are almost always determined by the method of dichromate oxidation and are subject to extreme variability (from tenths of a percent to more than 90% in man-made soil formations), but the average carbon content in the surface soil horizons can be estimated at 5–7%. The surface humus-accumulative horizons are represented by a variety of morphological forms with the content of organic matter of various origins. The work also focuses on those forms of organic matter, the content of which is extremely small, but very important for the biogeochemical functioning of soils-polycyclic aromatic hydrocarbons and components of petroleum products, as well as labile forms of soil organic matter. We recommend that further studies of the organic matter system be conducted in urbanized areas since the carbon cycle there is severely disrupted, as well as carbon flows. The urbanization and industrialization processes in the Arctic are progressing, which could lead to a radical transformation of carbon ecosystem services.